2017
DOI: 10.1515/jpem-2017-0238
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus therapy for congenital hyperinsulinism in an infant with a novel homozygous KCNJ11 mutation

Abstract: We report the successful use of sirolimus in the management of diazoxide unresponsive congenital hyperinsulinism with diffuse pancreatic involvement. We believe this is the youngest patient to be initiated on sirolimus so far.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
5
0
2
Order By: Relevance
“…Sirolimus has been reported to be an effective and safe drug for severe, diazoxide unresponsive, diffuse CHI with no major side effects ( 147 ). Following the first report, significant numbers of cases have been reported ( 148 , 149 , 150 , 151 , 152 , 153 , 154 ). As sirolimus has potentially adverse effects (perhaps related to dose) arising from its immunosuppressive effects, measurement of the blood levels is vitally important for reaching an optimal therapeutic level.…”
Section: Introductionmentioning
confidence: 99%
“…Sirolimus has been reported to be an effective and safe drug for severe, diazoxide unresponsive, diffuse CHI with no major side effects ( 147 ). Following the first report, significant numbers of cases have been reported ( 148 , 149 , 150 , 151 , 152 , 153 , 154 ). As sirolimus has potentially adverse effects (perhaps related to dose) arising from its immunosuppressive effects, measurement of the blood levels is vitally important for reaching an optimal therapeutic level.…”
Section: Introductionmentioning
confidence: 99%
“…A study from India has reported successful use of sirolimus in an infant with hyperinsulinism with diffuse pancreatic involvement and a novel KCNJ11 mutation 10. The genetic testing by next generation sequencing reported by Korula et al was a novel homozygous KCNJ11 variant (c.758C>A, p.Ala253Asp) 10.…”
Section: Discussionmentioning
confidence: 99%
“…A study from India has reported successful use of sirolimus in an infant with hyperinsulinism with diffuse pancreatic involvement and a novel KCNJ11 mutation 10. The genetic testing by next generation sequencing reported by Korula et al was a novel homozygous KCNJ11 variant (c.758C>A, p.Ala253Asp) 10. Another case series describing 10 subjects with congenital hyperinsulinism reported that mTOR inhibitor treatment in severe diffuse CHI was successful only in a minority (30%) of patients and concluded that they are unlikely to involve a decrease in islet cell proliferation 11.…”
Section: Discussionmentioning
confidence: 99%
“…Because complications mainly developed while combined with other medications, the latter may also be held responsible of some of these. For instance, the CHI case published by Korula et al [32] had a nonfermenting gram-negative bacilli sepsis before sirolimus treatment and had not had any infections or side effects in the 14 months of treatment on sirolimus. Further studies analyzing the long-term use of sirolimus in children with CHI are needed.…”
Section: Discussionmentioning
confidence: 99%